THE PECULIAR FORMATION OF THE WATER REGIME IN SODDY-PODZOLIC SOIL IN DIFFERENT POSITIONS OF SOIL CATENA - N. A. Muromtsev; K. B. Anisimov (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Under consideration is the dynamics of moisture reserves and soil water potential in different parts of the catena represented by soddy-podzolic slightly gleyed soil. Peculiar features in the development of moisture reserves have been identified in different elevated positions of this catena and their transformation in time depending on the weather conditions. It is shown that the dynamics of soil water potential in dependence on the depth of the soil profile and time well agrees with the peculiar changes in moisture reserves.